WATERING THE COTTON BY DRIP IRRIGATION METHOD (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article is mainly written about the distinct advantages and disadvantages of resurstejamkor irrigation technologies in Goose irrigation. It is also written that the economy of Water Resources will be if drip irrigation works are carried out.